A new device for the removal of cochlear schwannoma: A temporal bone study - Sudhoff, Holger; Riemann, Conrad; Kim, Rayoung; Scholtz, Lars Uwe; Pfeiffer, Christoph J.; Goon, Peter; Todt, Ingo (Frontiers in Surgery, 2023)
Background Intralabyrinthine schwannoma (ILS) is a rare, mostly unilateral disease that causes deafness. Different intralabyrinthine sites of ILS can occur and can be removed by different surgical approaches. Cochlear ILSs are frequently partially hidden by the modiolus and therefore difficult to extirpate. Surgical techniques can be traumatic, offer limited surgical control during removal, and are time-consuming. The aim of this present study was to demonstrate the performance and handling of a newly developed device for the removal of cochlear intralabyrinthine schwannoma in the temporal bone. Methods In a temporal bone study with a prepared posterior tympanotomy, an enlarged round window approach, and additional second turn access, a stiffened device with silicone rings was inserted and extracted gradually from the second turn access until the rings were visible in the second turn access. Results Insertion and extraction of the second cochlear access were easily performed. Pulling and pushing the silicone rings through the modiolus and hidden parts of the basal turn was possible and worked like a pipe cleaner. Conclusion This newly developed tissue removal device in combination with the proposed surgical handling offers a new and less traumatic way to remove cochlear ILS.